Analisis LQ (Location Quatient) dalam Menentukan Sektor Unggulan di Kabupaten Langkat, Provinsi Sumatera Utara (2015-2024) - Harahap, Muhammad Yusuf; Rahayu, Tri; Tobing, Ranti Delima; Sinaga, Ogin Syaputra; Sinulingga, Sam Deva Nasra; Sinaga, Hottarida; Saragih, Ian Josephan (Innovative: Journal Of Social Science Research, 2025)
This study aims to identify the leading sectors in Langkat Regency, North Sumatra Province, during the period 2015 to 2024 using the Location Quotient (LQ) method. This analysis was conducted to understand the comparative advantage of each economic sector in Langkat Regency and determine the potential for sustainable development. The data used in the form of GRDP (Gross Regional Domestic Product) based on current prices of various economic sectors taken from the publication of the Central Bureau of Statistics (BPS). LQ calculations were carried out for each sector in the time span, with sector classification standards following KBLI 2015. The results of this analysis show that there are several sectors that produce an LQ value of more than 1, which indicates that the sector is a leading sector and the basis of the regional economy. The prominent leading sector is the mining and quarrying sector which shows a high relative advantage. These findings provide a basis for policy makers and regional economic developers in designing optimal development strategies, as well as strengthening local resources to be able to compete and meet domestic and external needs. This research confirms the importance of data utilization and quantitative analysis in directing sustainable regional economic development.